Possible role of anti-SSA/Ro antibodies in the pathogenesis of pulmonary hypertension. (2016) - Guerreso, Kelsey; Conner, Edward Alexander
Abstract: Introduction: There are many different causes of pulmonary hypertension and the pathogenesis of the disease is still being elucidated. Although they are not the most common, autoimmunity and inflammation have been identified as possible causes. No one autoantibody has been identified as the definite cause of pulmonary hypertension. We present a rare association of anti-SSA/Ro antibodies and isolated pulmonary hypertension. Case presentation: A 53 year old African American female presented with abdominal pain, nausea, weight loss, dyspnea and fatigue. Upon further exam she was found to have high titers of antinuclear antibodies and anti-SSA/Ro antibodies. This antibody profile would typically be suggestive of Sjögren's Syndrome, which is characterized by dry eyes and poor salivary gland function. However, since this patient did not have any symptoms consistent with the disease a diagnosis of Sjögren's Syndrome could not be made. A combination of laboratory, imaging and diagnostic studies were done that revealed a final diagnosis of pulmonary hypertension. Conclusion: It is known that pulmonary hypertension has association with autoimmune diseases, however no clear markers yet exist. Anti-SSA/Ro antibodies have been rarely described in cases of pulmonary disease, and less so in pulmonary hypertension. This case describes a unique association between isolated pulmonary hypertension and anti-SSA/Ro antibody, thereby illustrating the need to investigate this autoantibody and others in the pathogenesis of autoimmune pulmonary hypertension.